2002
DOI: 10.1046/j.1365-8711.2002.05297.x
|View full text |Cite
|
Sign up to set email alerts
|

The Las Campanas Infrared Survey - II. Photometric redshifts, comparison with models and clustering evolution

Abstract: The Las Campanas Infrared (LCIR) Survey, using the Cambridge Infra‐Red Survey Instrument (CIRSI), reaches H∼21 over nearly 1 deg2. In this paper we present results from 744 arcmin2 centred on the Hubble Deep Field South for which UBVRI optical data are publicly available. Making conservative magnitude cuts to ensure spatial uniformity, we detect 3177 galaxies to H=20.0 in 744 arcmin2 and a further 842 to H=20.5 in a deeper subregion of 407 arcmin2. We compare the observed optical–infrared (IR) colour distr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
56
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 125 publications
12
56
1
Order By: Relevance
“…Using a much shallower sample than that from the HDF, but one that covers an area ∼ 140 times wider than it, and Firth et al (2002) showed that EROs are much more abundant than previously found in smaller fields and are much more strongly clustered than generic galaxies to the same limiting magnitude K ∼ 19. This made them likely candidates for high-z ETGs, and assuming that ∼ 70% of EROs are indeed ETGs at z > 1, Daddi, Cimatti & Renzini (2000) concluded that most field ellipticals were fully assembled by z ∼ 1.…”
Section: Evolution Of the Number Density Of Etgs To Z ∼ 1 And Beyondmentioning
confidence: 89%
“…Using a much shallower sample than that from the HDF, but one that covers an area ∼ 140 times wider than it, and Firth et al (2002) showed that EROs are much more abundant than previously found in smaller fields and are much more strongly clustered than generic galaxies to the same limiting magnitude K ∼ 19. This made them likely candidates for high-z ETGs, and assuming that ∼ 70% of EROs are indeed ETGs at z > 1, Daddi, Cimatti & Renzini (2000) concluded that most field ellipticals were fully assembled by z ∼ 1.…”
Section: Evolution Of the Number Density Of Etgs To Z ∼ 1 And Beyondmentioning
confidence: 89%
“…At higher redshifts, correlation lengths r 0 have been measured for different galaxy populations such as the LBGs and EROs. Values of about r 0 =4 h −1 Mpc (Porciani & Giavalisco 2002) and r 0 =11 h −1 Mpc (Daddi et al 2000;Firth et al 2002;Roche et al 2003) are reported with mean redshift of about 3 and 1-1.5 for the LBGs and EROs, respectively. Getting information on the clustering of the infrared galaxies is essential to see how they relate to the other galaxy populations and to understand their formation process.…”
Section: Clusteringmentioning
confidence: 97%
“…Previous studies have all found that EROs are very strongly clustered (e.g., Daddi et al 2000Daddi et al , 2002Firth et al 2002;Roche et al 2002;Brown et al 2005;Georgakakis et al 2005;Kong et al 2006Kong et al , 2009Kim et al 2011). However, the existing estimates of the clustering strengths, as measured by the scale r 0 where the two-point correlation strength is unity, show a broad range (r 0 = 5.5-17 h −1 Mpc) that makes it difficult to link the higher redshift EROs with local galaxy populations.…”
Section: Introductionmentioning
confidence: 99%
“…The present range of ERO selection criteria include (but are not limited to) (R − K) Vega > 5.0 (e.g., Brown et al 2005), (I − K) Vega > 4.0 (e.g., Kong et al 2009), (R −H ) Vega > 4.0 (e.g., Firth et al 2002), and (R − [3.6]) Vega > 6.5 (e.g., Wilson et al 2004). The consequences of using different ERO selection criteria have been considered in some studies (e.g., Yan & Thompson 2003;Wilson et al 2004;Conselice et al 2008;Kim et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation